A obra de Lev Semionovitch Vigotski: conceitos e interpretações - Schmidt, Jeani Escher (2019)
This research brings forward as a central theme, misrepresented and misleading translations and interpretations of important concepts from Lev Semionovitch Vigotski’s work. As well as featuring a discussion about the censorship and prohibition of his writings, which resulted in courts and exclusion of political, ideological and Marxist content of Vigotski’s ideas. Therefore, after identifying the problems of bigger impact related to his work, we investigated how Vigotski conceived, in his time, when creating the Cultural-Historical Psychology, the concepts of Instruction, Speech, Play (activity of make-believe), Creation and Imminent Development Area, and how, from the 1980s, authors adept to his thinking have worked with these concepts. The research is characterised as theoretical- bibliographic, of exploratory nature and qualitative approach, based on the Spanish translation of Vigotski’s work, and on Brazilian translations and productions existing on the subject. We seeked to know the context of the life and work of the author; which Historical-Dialectical Materialism contributions influenced the Cultural- Historical Psychology; the similarities and differences between the meanings of each concept and its nomenclature. The results highlighted that on the translation from Russian to Spanish, Vigotski uses the concepts of language and speech with its nomenclature and different meanings. In Brazilian productions, authors don’t reference the speech process, just utilizing the term and meaning of language to refer to the process speech studied by Vigotski. About the concepts of instruction and learning, we noted that both Spanish and Russian use the term instruction. In Portuguese, the term utilized is learning. In both languages the meaning of the terms is inconsistent with the meaning that the term instruction has in the Russian language. In relation to the concepts of play (activity of make-believe) and toy, our research has shown that the concept was translated to Spanish as game. In Portuguese the nomenclature used is toy, and even though the correct translation from Russian to Portuguese is play (activity of make-believe), the meaning of the concept matches in the three languages. As for the creation and art concepts, we showed the use of both terms in Spanish and in Portuguese. Both languages feature classifications and meanings consistent with the concepts brought from the Russian. The development zones have, both in Spanish and Portuguese, inconsistent nomenclatures and meanings which don’t transcribe Vigotski’s idea when creating the concept. The term translated by Prestes (2010) as imminent development zone appears as the most trustworthy in relation to the author’s theory. Moreover, we have identified details and information concerning Vigotski’s work that are little known, such as: the translation work, the path to the publishing of his works, the writing of his name, the conflicts regarding troika, dates and data, amongst others.